Manajemen Konflik dan Implementasinya dalam Proses Pembelajaran - Afifah Qodri Rinjani; Sariasih, Yanti; Haryanti, Sri (Nusa Putra University, 2024)
Conflict management in the learning process is an important aspect that has a significant impact on the quality of education. Conflicts can arise between students, between students and teachers, and between teachers and school management. Effective conflict management can improve the quality of learning and create an environment conducive to the personal and professional development of all parties. Conflict, if managed well, can trigger positive change and innovation. Several conflict management styles, such as competition, collaboration, compromise, avoidance and accommodation, are important for educators to understand in order to determine the right approach. Factors such as cultural differences, ineffective communication, and competition for resources can trigger conflict. Poorly managed conflict can decrease student motivation, engagement and achievement. Effective conflict management strategies include teacher training, emotional intelligence education, and restorative approaches. Implementing conflict management theory through these strategies can create a more harmonious, inclusive and productive learning environment, as well as improve academic outcomes and student well-being.